2018
DOI: 10.3390/ijms19020476
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zinc Homeostasis in the Pathogenesis of Diabetes and Obesity

Abstract: Zinc deficiency is a risk factor for obesity and diabetes. However, until recently, the underlying molecular mechanisms remained unclear. The breakthrough discovery that the common polymorphism in zinc transporter SLC30A8/ZnT8 may increase susceptibility to type 2 diabetes provided novel insights into the role of zinc in diabetes. Our group and others showed that altered ZnT8 function may be involved in the pathogenesis of type 2 diabetes, indicating that the precise control of zinc homeostasis is crucial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(123 citation statements)
references
References 84 publications
1
119
1
2
Order By: Relevance
“…Obesity has been associated with lower levels of Se, Fe, and Zn in the general population [54,55,[59][60][61], though there are also discrepancies which is consistent with our negative relationship between maternal prepregnancy BMI and Se or Fe [62]. The statistically and positive relationships between Cu levels and prepregnancy BMI found in our study are also confirmed in the literature and is explained by the increase in Cu-binding ceruloplasmin (acute phase protein) [63].…”
Section: Discussionsupporting
confidence: 90%
“…Obesity has been associated with lower levels of Se, Fe, and Zn in the general population [54,55,[59][60][61], though there are also discrepancies which is consistent with our negative relationship between maternal prepregnancy BMI and Se or Fe [62]. The statistically and positive relationships between Cu levels and prepregnancy BMI found in our study are also confirmed in the literature and is explained by the increase in Cu-binding ceruloplasmin (acute phase protein) [63].…”
Section: Discussionsupporting
confidence: 90%
“…On the pancreatic front, there are two common disorders in which MR detection of Zn 2+ secretion may help inform: diabetes mellitus and chronic pancreatitis. It is very well known that Zn 2+ is a crucial factor in the crystallization and storage of insulin [ 78 , 79 ], showing a broader impact of zinc on both types of diabetes [ 12 ]. β-cell function, glucose metabolism, insulin activity, and pathogenesis of diabetes are directly linked to zinc homeostasis [ 12 , 102 , 103 ].…”
Section: Detection Of Zinc With Magnetic Resonance Imagingmentioning
confidence: 99%
“…Studies by others and our group suggest that AβPs directly incorporate into the membrane and form channels (pores) that allow the passage of Ca 2+ and other cations, and that the resulting change in [Ca 2+ ] i may be a primary pathogenetic event in AβP neurotoxicity [110][111][112]. Neurotoxic peptide fragments of AβP, including AβP(1-40), AβP (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and AβP , have been demonstrated to incorporate into artificial planar lipid membranes and form giant multi-level pores (~5 nS) with cation (including Ca 2+ ) selectivity [113][114][115]. To assess the validity of this amyloid channel hypothesis, we performed an electrophysiological study to examine whether AβPs form channels on neuronal cell membranes as well as on liposomes.…”
Section: Aβp-induced Ca Dyshomeostasismentioning
confidence: 98%
“…ZIP transporters control Zn 2+ influx into cells or subcellular organs such as the Golgi apparatus or endoplasmic reticulum (ER). Disorders of Zn 2+ transporters have been shown to cause Ehlers-Danlos syndrome and other human diseases [25]. Metallothioneins (MTs), such as MT1, MT2, and MT3, also regulate Zn 2+ homeostasis [26].…”
Section: Neurometals In the Brainmentioning
confidence: 99%